STUDI PENERAPAN STANDAR PENILAIAN PENDIDIKAN DI SDN KALONGAN 02 KECAMATAN UNGARAN TIMUR - Qun Firmani Lestari; Jaya Yanti Nur Istiqomah; Ana Marwani; Ngatijah, Ngatijah; Sudjono, Sudjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Difficulty in understanding the structure of the curriculum can affect the standard of assessment carried out. This research was carried out not only to look for difficulties in implementing assessments for students but also to look for the conformity of elementary school student assessments carried out by teachers in the Merdeka Curriculum with the assessment standards set by the Ministry. The problem to be studied focuses on the implementation of assessment of student learning outcomes in the learning process at SD Negeri Kalongan 02, East Ungaran District. The aim that is expected to be achieved in this research is to find out how to assess student learning outcomes in the learning process at SD Negeri Kalongan 02 Ungaran Timur. In this research, the author used qualitative research methods. The research method uses qualitative methods and a descriptive approach. Qualitative methods are often called naturalistic research methods because the research is carried out in natural conditions (natural settings). The school makes all assessments a consideration in determining student achievement or graduation, so not only from exam scores, to formulate all the scores that will be used as material for student graduation, the school accumulates all student scores through the report card application that has been provided. The assessments carried out at SD Negeri Kalongan 02 have met existing standards, but there are obstacles when carrying out assessments of student learning outcomes, namely when there are students who still do not meet the KKTP.